Biological diversity or nomenclatural multiplicity: the Thai freshwater snail Neoradina prasongi Brandt, 1974 (Gastropoda: Thiaridae). Issue 3 (3rd April 2019) - Wiggering, Benedikt; Neiber, Marco T.; Krailas, Duangduen; Glaubrecht, Matthias
Abstract : A key aspect of evolutionary systematics research is the distinction between nomenclatural multiplicity and biological diversity. Unravelling the latter is only possible by identifying true biological entities, i.e., species and evolutionary lineages instead of an accumulation of nominal taxa. This is particularly difficult to achieve for species with high phenotypic plasticity, such as thiarid freshwater snails, a speciose family notorious for its taxonomic diversity. Exceptionally fraught with problems is a complex of nominal species in the genera Melanoides and Stenomelania. In addition to these genera, morphologically almost indistinguishable shells were the basis for the description of Neoradina prasongi and the establishment of Neoradina. To test whether these shells represent specimens from a distinct evolutionary lineage, we studied representative material of all three genera from Thailand, i.e., Neoradina prasongi and syntopically occurring and/or conchologically similar species, using molecular genetics, shell characters via geometric morphometrics, radula morphology, and reproductive biology. The molecular study of mitochondrial 16S rRNA and COI gene fragments unambiguously supports the distinction of the six species examined, most notably Neoradina prasongi as a distinct lineage. Geometric morphometrics of shell shapes allowed distinguishing species currently assigned to Stenomelania s. str. from the other studied species. Radula characters were uninformative. Our findings confirm the prevalence of different reproductive modes in these viviparous freshwater snails (i.e., the release of larval or juvenile stages). The combined results of our genetic analyses were ambiguous for implications on genus affiliations and did not support the classification of some species as part of Stenomelania, affecting the taxonomic stability of the current conception of these genera. Our results are a crucial first step towards a better understanding of the diversity found within these taxonomically problematic thiarids, emphasizing the need for evolutionary systematics approaches, in order to properly evaluate truly biological diversity in contrast to nomenclatural multiplicity.